Possibilities of Venture Investments for Slovak Small and Medium-Sized Enterprises and Effect on Their Capital Structure - Veronika VRABLOVA (Communications of International Proceedings, 2020)
Financing of small and medium sized enterprises (SME) is very discussed topic. In these times we can see that SME more concerning about alternative ways of financing such as venture capital. Because of this, we decided to focus on this financing among Slovak SME. Aim of this paper is to describe available venture capital opportunities for small and medium size and identify the effect of venture capital investments on capital structure of an enterprise. Main methods used to fulfill the aim were analysis of available studies and available literature. The effect of venture investments on company capital structure was demonstrated on case study of Slovak startup. We have reached several findings. Firstly, venture capital investments are very low in Slovakia, although there are several funds providing this financing. In 2017, SMEs raised only 2,9 million € by venture capital. Secondly, Slovak SME do not have high demand for this financing. And finally, the use of venture capital reduces indebtedness of the company.
Keywords: Venture capital; small and medium-sized enterprises; capital structure